Static and Dynamic Analysis and Topological Optimization of Gearbox Housing in Electric Vehicle - Xianchang Peng; Wenqi Cai; Zhibin Lin; Bingzhao Gao (Jixie chuandong)
Taking a new type of two speed transmission without power interruption in electric vehicles as research object， in order to improve its stability and economy， the housing is designed and optimized. Firstly， the housing structure is designed and its finite element model is established. On this basis， the stiffness and strength of the housing are calculated and the constrained modal calculation is more in line with the engineering practice. The accuracy of the finite element model is verified by the constrained modal test. The simulation and test results show that the stiffness of the housing is low， and the first two natural frequencies are very close to the excitation frequency of gear meshing at the common speed. According to the results of static and dynamic multi-objective topology optimization， the housing structure is improved. The calculation results of the improved housing show that the strength is basically unchanged， the maximum displacement of the bearing hole area is reduced from 0.085 mm to 0.07 mm， the natural frequencies of the first two orders are increased by 24.8 Hz and 50.2 Hz respectively， which reduces the risk of resonance and reduces the mass by 7.5%.